Penguatan Kompetensi Guru TK dan SD dalam Menerapkan Pembelajaran Ramah Anak dan Bebas Kekerasan melalui Workshop “Menjadi Guru Hebat Tanpa Kekerasan” di Sekolah Mutiara Global Pekanbaru - Asmidaryani Asmidaryani; Sintong Tampubolon; Umi Habibah; Melsi Syawitri; Elmirawati Elmirawati (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2026)
Violence in education remains a common issue, including physical, verbal, and psychological violence. This condition can negatively affect students’ emotional development and learning motivation. Therefore, efforts are needed to improve teachers’ understanding of non-violent education and positive communication in the learning process. This community service activity aimed to improve the understanding and skills of kindergarten and elementary school teachers at Sekolah Mutiara Global Pekanbaru in implementing humanistic, child-friendly, and violence-free learning through the workshop entitled Becoming Great Teachers Without Violence. The method used in this activity was Participatory Action Research (PAR), consisting of observation, problem identification, problem formulation, workshop implementation, and evaluation stages. Data were collected through observation, interviews, discussions, and documentation. The results showed an increase in teachers’ understanding of non-violent education, positive communication, emotional management, and positive discipline in learning. Teachers also experienced changes in their perspectives regarding school discipline by applying more empathetic and humanistic approaches toward students. This activity proved that participatory-based workshops can help teachers create a safe, comfortable, and supportive learning environment for students’ character development